The Role of Green Society in Society 5.0: Tango Diamond in a Collective Intelligence (Hybrid) Ecosystem Founded on Human-Centricity and Sustainability - Vesna, Tornjanski; Snežana, Knežević; Vuk, Mirčetić; Kenneth, Drinkwater; Haitham M., Alzoubi; Davron Aslonqulovich, Juraev; Rohitash Kumar, Verma; Hussein, Alkhozahe; Evangelos, Siozos; Tarek, Yalouli (INTI International University, 2024)
The research composition sets out to extend and deepen the extant theoretical fund with a holistic perspective of the role of green society within the framework of Society 5.0. The purpose of the article is to move forward with tango diamond in a Collective Intelligence (Hybrid) Ecosystem concept and model, founded on human-centricity, sustainability and long-term prosperity and wellbeing. The study opted for a research method that is grounded on a systematic literature review approach, by utilizing a five-stage review process, taking into account the conceptual nature of the article. The research results signify that the role of green society goes beyond the traditional understanding of society and requires a notable transformation towards the desired effects of human-centric society doctrines. The innovative green society within Society 5.0 is substantial and multifaceted. The holistic sight of the contribution of green society goals and principles of a human-centric society is systematically depicted in the study, by pointing out that the framework is far more than a pattern and goes beyond conventional prospects, towards the development of a highly smart and healthy society and world. The research can make significant contributions to advancing understanding of green society, and the transition to a more equitable, healthy, sustainable and resilient future. The work may influence academic discourse, policy debates, and practical initiatives aimed at promoting sustainability and addressing global "green" and humanity challenges. The paper may contribute to all stakeholders interested in developing and implementing a healthy green society in a healthy human-centric society by approaching inclusive collaboration in a connected world and encouraging open innovation in managing change.